2015
DOI: 10.1109/mcom.2015.7045405
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sliceable bandwidth variable transponders

Abstract: This article reports the work on next generation transponders for optical networks carried out within the last few years. A general architecture supporting super-channels (i.e., optical connections composed of several adjacent subcarriers) and sliceability (i.e., subcarriers grouped in a number of independent super-channels with different destinations) is presented. Several transponder implementations supporting different transmission techniques are considered, highlighting advantages, economics, and complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 215 publications
(152 citation statements)
references
References 14 publications
0
149
0
3
Order By: Relevance
“…To ensure higher utilization and financial viability, multi-flow transponders or SBVTs, have been proposed. An SBVT is capable of generating multiple optical flows that can be routed to different destinations, thus sharing the capacity of a single transponder between multiple source-destination pairs [14], [15], [24]. …”
Section: B Flexible Transceiversmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure higher utilization and financial viability, multi-flow transponders or SBVTs, have been proposed. An SBVT is capable of generating multiple optical flows that can be routed to different destinations, thus sharing the capacity of a single transponder between multiple source-destination pairs [14], [15], [24]. …”
Section: B Flexible Transceiversmentioning
confidence: 99%
“…The reference SBVT architecture for our study is shown in Fig. 4 [24]. The client signals (OTN or Ethernet) are adapted for the photonic layer by a sliceable OTN interface (not shown) that creates different data streams, by fragmenting incoming traffic.…”
Section: ) Sbvt Architecturementioning
confidence: 99%
“…Different combination of multiple optical paths with variable/equal bandwidth are formed and routed or sliced to the same or different destinations. Various architectures for SBVT designs have been proposed and demonstrated in [38][39][40]. Also a cost analysis of SBVT in a network scenario has been presented in [41], showing that SBVT reduce the cost of transponders by 30%.…”
Section: Review On Enabling Technologiesmentioning
confidence: 99%
“…The adaptation of the optical launch power [12], [13] and mitigation of nonlinear interference using, for example digital back propagation (DBP) [14], [15], can improve the properties of the light path. The use of flexible grids with adaptive signal bandwidth [16], superchannels and sliceable transceivers [17] allows the light path bandwidth to be better matched to the clients data requirements. With all of these the size of the adaptation control steps are important and it has been shown that finer steps improves network throughput [18], [19].…”
Section: Introductionmentioning
confidence: 99%